Autolesão não suicida em adolescentes: um fenômeno multifacetado - Bruna Mascarenhas Campos (2023)
This research aims to understand whether there is an association between the phenomenon of non-suicidal self-injury (NSSI) and suicide in adolescence. To achieve this purpose, an integrative literature review was conducted, addressing self-inflicted violence in adolescence, defining concepts, and characterizing the behavior of NSSI and suicide. Furthermore, functions and risk factors associated with NSSI were identified and discussed. Adolescence is a phase marked by physical, psychological, cognitive, and social changes, presenting challenges and dilemmas that can lead to self-destructive behaviors, such as NSSI and suicide. Suicide is a conscious and voluntary act seeking death, while NSSI involves planned or impulsive behaviors without the intent to die, aimed at alleviating painful emotional states. According to the literature, risky behaviors, such as self-injury, can, in some cases, escalate in severity and, in more extreme situations, lead to outcomes such as suicide. Despite the absence of an intent to die in NSSI, it still represents a significant risk factor for self-extermination. Regarding the functions associated with self-injury, research shows that multiple functions can coexist in the same act. The primary function found in studies was emotional regulation, which pertains to the individual's ability to understand and cope with their emotions without affecting their life. Other functions, such as protection against suicide, self-punishment, alteration of cognitive states, generation of feelings, communication, and influence on the external environment, were also identified. It is noteworthy that these functions have elements directly related to emotional regulation and, despite their uniqueness, complement each other. As for risk factors, it is important to highlight the possibility of the coexistence of various factors in the same individual. Among the main risk factors associated with NSSI are social, individual, family-related, psychopathological, a history of violence, and negative childhood experiences.